Parameters of Somatosensory Evoked Potentials in Patients with Primary Sjӧgren's Syndrome: Preliminary Results. (5th April 2018) - Dziadkowiak, Edyta; Sebastian, Agata; Wieczorek, Małgorzata; Kusińska, Elżbieta; Waliszewska-Prosół, Marta; Wiland, Piotr; Ejma, Maria
Abstract : Primary Sjogren's syndrome (pSS) is a chronic autoimmune disease. The aim of the study was to establish whether in patients with pSS without central nervous system (CNS) involvement, the function of the central portion of the sensory pathway can be challenged. In 33 patients with pSS without clinical features of CNS damage and normal head computed tomography scan, somatosensory evoked potentials (SEP) were studied. The results were compared to other clinical parameters of the disease, particularly to immunological status. The control group consisted of 20 healthy volunteers. Mean latency of all components of SEP was considerably prolonged in patients compared to the control group. Mean interpeak latency N20-N13 (duration of central conduction TT) did not differ significantly between the groups. However, in the study group, mean amplitude of N20P22 and N13P16 was significantly higher compared to healthy individuals. In patients with pSS, significant differences in SEP parameters depending on the duration of the disease and presence of SSA and SSB antibodies were noted. The authors confirmed CNS involvement often observed in patients with pSS. They also showed dysfunction of the central sensory neuron as a difference in the amplitude of cortical response, which indicates subclinical damage to the CNS.